Opposite latitudinal patterns for bird and arthropod predation revealed in experiments with differently colored artificial prey - Zvereva EL; Castagneyrol B; Cornelissen T; Forsman A; Hernandez-Aguero JA; Klemola T; Paolucci L; Polo V; Salinas N; Theron KJ; Xu GR; Zverev V; et al. (WILEY, 2022)
The strength of biotic interactions is generally thought to increase toward the equator, but support for this hypothesis is contradictory. We explored whether predator attacks on artificial prey of eight different colors vary among climates and whether this variation affects the detection of latitudinal patterns in predation. Bird attack rates negatively correlated with model luminance in cold and temperate environments, but not in tropical environments. Bird predation on black and on white (extremes in luminance) models demonstrated different latitudinal patterns, presumably due to differences in prey conspicuousness between habitats with different light regimes. When attacks on models of all colors were combined, arthropod predation decreased, whereas bird predation increased with increasing latitude. We conclude that selection for prey coloration may vary geographically and according to predator identity, and that the importance of different predators may show contrasting patterns, thus weakening the overall latitudinal trend in top-down control of herbivorous insects.